Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/antiox11050988
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Antioxidant Compounds from Chestnut Peels through Semi-Industrial Subcritical Water Extraction

Abstract: Chestnut peels are a poorly characterized, underexploited by-product of the agri-food industry. This raw material is rich in bioactive compounds, primarily polyphenols and tannins, that can be extracted using different green technologies. Scaling up the process for industrial production is a fundamental step for the valorization of the extract. In this study, subcritical water extraction was investigated to maximize the extraction yield and polyphenol content. Lab-scale procedures have been scaled up to the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The influence of sample-to-solvent ratio and mass transport enhancement on chestnut shells extraction was also evaluated in Microwave-Assisted Subcritical Water Extraction (MASWE) using a range of temperatures between 100 °C and 220 °C [ 34 ]. According to the authors, it was evidenced an increase of the extract production proportional to the increase of temperature, but minor deviations were observed for the sample-to-solvent ration (1:20–1:30), with exception of the 150 °C extract (322.37 mg/g DW and 416.56 mg/g DW, respectively) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The influence of sample-to-solvent ratio and mass transport enhancement on chestnut shells extraction was also evaluated in Microwave-Assisted Subcritical Water Extraction (MASWE) using a range of temperatures between 100 °C and 220 °C [ 34 ]. According to the authors, it was evidenced an increase of the extract production proportional to the increase of temperature, but minor deviations were observed for the sample-to-solvent ration (1:20–1:30), with exception of the 150 °C extract (322.37 mg/g DW and 416.56 mg/g DW, respectively) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, little has been described in the literature about the use of this technology at the industrial level from agri-food industry waste. Cravotto et al 12 studied the scale-up process from the laboratory scale to semi-industrial subcritical water extraction system, but only the extraction yield, the polyphenol content, and the antioxidant capacity of the collected extracts were evaluated. Moreover, Thiruvenkadam et al 13 analyzed the recent developments in subcritical water extraction scale-up, concluding that, although the extraction by means of subcritical water has been investigated, there is still a commercial interest and a need for the development of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly used for food, especially processed foods, and in medicine. In 2019, the FAO (Food and Agriculture Organization of the United Nations) reported that 2,321,780 tons of chestnuts were produced globally [ 1 ]. Korea is the second-largest chestnut producer in Asia, producing 50,000 tons of chestnuts annually [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 45% of Korean chestnuts are exported as peeled, canned, and raw chestnuts [ 3 ]. The integument of chestnuts consists of a hard hull (outer shell) and thin skin (inner shell), which make up 15–20% of the fresh fruit weight [ 1 , 4 ]. During industrial chestnut peeling processes, the shells are considered solid waste and thrown away.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation